Proposed Metrics for Agile Business Intelligence - Samya Hadi Najar; Mostafa Obaid Gawad (International Journal of Computers and Informatics, 2023)
Business Intelligence has become the front of demanding technologies. The large or midsize companies need technology to adapt to changing requirements, to deal with a rich amount of data; to get correct information, to analyze data, and finally to quickly support decision makers. Developing an agile BI application can be defined as a short-delivering software application. This process is based on frequently adapting to changing requirements, involving customer participation, and delivering high-quality applications. Agile teams need a set of reliable metrics to measure their performance at different three levels: functionality, content, and scalability. This paper proposes Goal Question Agility Metrics that can be used in measuring the performance of agile teams working in developing business intelligence applications. Goal Question Agility Metrics is based on the Goal Question Metrics method that was developed by Victor Basili in 1994 [19]. In addition, Goal Question Agility Metrics depend on agile and BI concepts. GQAM proposes a set of metrics that are used to measure performance. The GQAM will be subjected to experiments using a real data set in the future.
Keywords: Business Intelligence; Software Application; Agile Methods; Goal Question Metrics; Team Performance